2014
DOI: 10.1007/s00520-014-2504-9
|View full text |Cite
|
Sign up to set email alerts
|

Prospective surveillance of breast cancer-related lymphoedema in the first-year post-surgery: feasibility and comparison of screening measures

Abstract: BCRL screening is acceptable and valued by breast cancer survivors. Work needs to continue to establish the most effective screening tool and the natural behaviour of BCRL within the first-year post-surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 38 publications
0
36
0
Order By: Relevance
“…The authors hypothesized this was due to the fact that some of the LE cases were localized to one region of the extremity that could not be differentiated by BIA. In the final conclusion, there was no significant correlation between CM and BIA with agreement in only 25.8% of cases . Table summarizes the studies of SFBIA compared to circumference.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The authors hypothesized this was due to the fact that some of the LE cases were localized to one region of the extremity that could not be differentiated by BIA. In the final conclusion, there was no significant correlation between CM and BIA with agreement in only 25.8% of cases . Table summarizes the studies of SFBIA compared to circumference.…”
Section: Resultsmentioning
confidence: 82%
“…In newer models of the machine, the impedance ratios are calculated as L‐Dex ratios. In this format, an L‐Dex score of −10 to +10 is considered normal, and a score above 10 is diagnostic for lymphedema .…”
Section: Introductionmentioning
confidence: 99%
“…In their study, lymphedema was identified in 29% of patients by arm circumference and in 11% patients by bioimpedance; agreement between the two measurements for lymphedema diagnosis occurred in 25.5% of cases. 7 In contrast, Fu et al did find that bioimpedance and arm circumference were correlated in their cross-sectional study; however, their patient population differed from the aforementioned studies and notably, baseline measurements were not obtained on the study participants 4 —a limitation of their findings. Although one “best” method for lymphedema diagnosis has not reached consensus, our study results raise concerns for bioimpedance as a single tool to diagnose BCRL.…”
Section: Discussionmentioning
confidence: 80%
“…Bioimpedance has been primarily studied as a diagnostic tool for lymphedema; however, most investigators have compared bioimpedance with circumferential arm measurements, 4,6,7 which has limited reproducibility among raters. Furthermore, longitudinal prospective studies evaluating bioimpedance as a predictor of lymphedema are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Moderate to strong correlations have been reported between BIA data and both self-report ( r = 0.71, research model46) and perometry results ( r = 0.71-0.93, research model34,42,43,47; r = 0.40-0.60, clinical model48). Correlation with circumferential measurement ranged from low (clinical model)49 to moderate (0.31-0.52, research model,50 clinical model41). …”
Section: Bioimpedance Analysismentioning
confidence: 99%